Problematika hukum dalam implementasi kebijakan subsidi pangan terhadap kesejahteraan ekonomi masyarakat: Tinjauan atas program sembako berdasarkan undang-undang nomor 18 tahun 2012 tentang pangan - laili, anis nur (Maliki Interdisciplinary Journal, 2025)
This study examines the legal challenges in the implementation of food subsidy policies through the Sembako Program, which is designed to fulfill the right to food for the poor as mandated by Law Number 18 of 2012 concerning Food. In practice, the program encounters several critical issues such as mistargeted beneficiaries, inaccurate data, weak oversight, and the absence of strict legal sanctions for violations. Employing a qualitative approach, the study applies normative juridical methods to analyze the regulatory framework, and sociological methods to assess the program's impact on community welfare. The findings reveal that the effectiveness of the Sembako Program remains suboptimal due to poor governance, regional disparities in distribution, and the rise of social dependency among beneficiaries. Therefore, policy reform is urgently needed, particularly in strengthening data systems, enhancing community empowerment, and improving transparency and accountability in public fund management. This research aims to contribute academically to the formulation of a more equitable, targeted, and law-based food subsidy policy aligned with the principles of good governance.